2020
DOI: 10.1029/2019jc016016
|View full text |Cite
|
Sign up to set email alerts
|

Tidal Effects on the Surface Water Cooling Northeast of Hainan Island, South China Sea

Abstract: Using a 3-D high-resolution ocean model, this paper explores the mechanisms that cause surface and subsurface water cooling northeast of Hainan Island during summer. Results show that two cooling centers in the regions east of Wenchang city and east of the Qiongzhou Strait occur when tides are included in the model. The cooling is primarily caused by large-scale changes in the circulation in the northwestern South China Sea (SCS) through anomalous horizontal pressure gradients caused by inhomogeneous tidal mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 47 publications
(74 reference statements)
1
9
0
Order By: Relevance
“…These results indicate that the upwelling in summer is stronger than that in spring. This conclusion is consistent with previous studies (Guan & Yuan, 2006;Li et al, 2020).…”
Section: Distribution Of Water Temperaturesupporting
confidence: 94%
See 2 more Smart Citations
“…These results indicate that the upwelling in summer is stronger than that in spring. This conclusion is consistent with previous studies (Guan & Yuan, 2006;Li et al, 2020).…”
Section: Distribution Of Water Temperaturesupporting
confidence: 94%
“…(2015) found that pronounced surface cooling and upwelling related fronts are present in the NWSCS in summer season. Previous studies indicated that wind forcing, eddies, topography, and tides are the important factors affecting the upwelling in NWSCS (Guan & Yuan, 2006; Li et al., 2020; Xu et al., 2013). In general, most studies are based on physical methods to study water processes and upwelling in the South China Sea.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variations of momentum components of oceanic processes caused by Malakas will be further investigated to determine the contributing factors in Eddies 1 and 2, including advection, the pressure gradient force, the Coriolis force, and vertical viscosity (Li, et al. 2020; Pietrafesa, 1973, 1990; Sun & Pietrafesa, 1992). The momentum equations for the surface layer (without vertical integration) are expressed in Equation for the x and y directions: leftutAC=u2xuvyHADuwzVAD1ρPxPGF+fvCOR+1ρτxzVVISCleftvt=v2yuvxvwz1ρPyfu+1ρτyz where P is the water pressure.…”
Section: Roms Model Simulation Resultsmentioning
confidence: 99%
“…In this study, we investigate the influence of the tides on the predictability of the subtidal ocean circulation in a region that experiences both dynamic mesoscale circulation and energetic internal tides. The Philippine Sea region provides an ideal case-study for this work as it exhibits strong internal tides (Alford et al, 2011(Alford et al, , 2015Ramp et al, 2004), tidal mixing in the South China Sea (SCS) (Li et al, 2020), the origins of an important Western Boundary Current system (Rudnick et al, 2011;Yuan et al, 2006) and high eddy activity due to baroclinic instability between the Subtropical Counter Current and the North Equatorial Current (Qiu & Chen, 2010).…”
mentioning
confidence: 99%